Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi in an old-growth Mediterranean forest dominated by Quercus ilex L. - Richard, F.; Moreau, P.-A.; Selosse, M.-A.; Gardes, M. (Canadian Journal of Botany, 2004)
We collected and mapped epigeous fruitbodies of both ectomycorrhizal (ECM) and saprobic fungi in an oldgrowth Quercus ilex L. Mediterranean forest within a permanent transect of 6400 m2 over three consecutive fruiting seasons. Out of 5382 fruitbodies, a total of 234 species were found, including 166 and 68 ECM and saprobic taxa, respectively. Both communities were mainly composed of rare species. Two genera, Russula and Cortinarius, accounted for 34.4% of ECM fruitbodies and 50% of species diversity. The three most abundant ECM species were Laccaria laccata (Scop.: Fr.) Berk. & Broome, Inocybe tigrina R. Heim, and Lactarius chrysorrheus Fr. The fruiting ECM community encompassed a few Mediterranean species and numerous broad host range temperate species. We also analysed the fruiting patterns in relation to forest structure, host composition, and natural canopy gaps. The results showed (i) a significant correlation of species richness to tree density, (ii) a richness decrease as the number of vegetation layers increases, and (iii) a preferential fruiting of some species near Q. ilex or Arbutus unedo L. Another noteworthy feature was that richness and production were greatly enhanced in canopy gaps. Selective fruiting was also observed among species. These results highlight the importance of forest structure and large woody debris for fungal conservation.
doi: 10.1139/b04-128doi: 10.1139/b04-128The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: canopy gaps; ECM community; fungal conservation; Holm oak; macromycete fruiting patterns; saprophytic fungi

Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi in an old-growth Mediterranean forest dominated by Quercus ilex L. - Richard, F; Moreau, P -A; Selosse, M -A; Gardes, M (Canadian Journal of Botany, 2004)
We collected and mapped epigeous fruitbodies of both ectomycorrhizal (ECM) and saprobic fungi in an oldgrowth Quercus ilex L. Mediterranean forest within a permanent transect of 6400 m2 over three consecutive fruiting seasons. Out of 5382 fruitbodies, a total of 234 species were found, including 166 and 68 ECM and saprobic taxa, respectively. Both communities were mainly composed of rare species. Two genera, Russula and Cortinarius, accounted for 34.4% of ECM fruitbodies and 50% of species diversity. The three most abundant ECM species were Laccaria laccata (Scop.: Fr.) Berk. & Broome, Inocybe tigrina R. Heim, and Lactarius chrysorrheus Fr. The fruiting ECM community encompassed a few Mediterranean species and numerous broad host range temperate species. We also analysed the fruiting patterns in relation to forest structure, host composition, and natural canopy gaps. The results showed (i) a significant correlation of species richness to tree density, (ii) a richness decrease as the number of vegetation layers increases, and (iii) a preferential fruiting of some species near Q. ilex or Arbutus unedo L. Another noteworthy feature was that richness and production were greatly enhanced in canopy gaps. Selective fruiting was also observed among species. These results highlight the importance of forest structure and large woody debris for fungal conservation.
doi: 10.1139/b04-128
Keywords: canopy gaps; ECM community; fungal conservation; Holm oak; macromycete fruiting patterns; saprophytic fungi